Attitudes of Service Business Operators Towards Policies Promoting the Use of Kip in Luang Prabang Capital - xayavong, Kanchana; DUANGVILAYKEO, Thipphavanh; PHENGSAVAT, Sithivikhone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aims to: (1) examine the perceptions and understanding of service business entrepreneurs in Luang Prabang regarding the use of the Lao Kip; and (2) investigate the level of opinions of these entrepreneurs toward the policy promoting the use of the Lao Kip issued by the Bank of the Lao PDR. The research adopts a survey design, employing a questionnaire as the primary data collection instrument. Data were collected from a sample of 80 service business establishments in Luang Prabang, including hotels, guesthouses, restaurants, and tourism companies. The data were analyzed using frequency, percentage, mean, and standard deviation. The findings reveal that: 1) The level of perception and understanding of service business entrepreneurs regarding the policy promoting the use of the Lao Kip in Luang Prabang is relatively high, accounting for 85.93%. Among the dimensions, the highest level of perception and understanding is found in promotional communication related to the policy (93.12%), followed by business financial aspects related to the policy (88.75%). The lowest, but still high, levels are in trust toward the policy and emotional responses to the policy, both accounting for 80.93%. 2) The overall attitudes of service business entrepreneurs in Luang Prabang toward the Lao Kip promotion policy of the Bank of the Lao PDR are at a high level ( = 3.96, SD = 0.57). The highest level of agreement is observed in the promotional aspect ( = 4.28, SD = 0.48), followed by motivational encouragement ( = 4.03, SD = 0.71), monitoring and follow-up ( = 3.98, SD = 0.56), and dissemination ( =3.98, SD = 0.72), respectively.